Análise de instrumentos de qualificação ambiental aplicáveis em lotes urbanos edificados: os casos da Quota Ambiental, do município de São Paulo (SP) e da qualificação Qualiverde, do município do Rio de Janeiro (RJ) - Pereira, Giovanna Vicentini (Universidade Federal de São Carlos, 2021)
ABSTRACT Migration to urban areas, motivated by global growth and industrialization, culminated in an increase in the Brazilian urban population and, consequently, an increase in environmental impacts. As a form of control and mitigation, public policies for environmental regulation have begun to emerge and, more recently, incentive instruments with a view to achieving greater urban sustainability. Therefore, this study aimed to analyze the potential and limitations of two instruments developed by Brazilian metropolises: the Quota Ambiental (QA) of the city of São Paulo (SP), and the Qualificação Qualiverde, of the city of Rio de Janeiro (RJ). The first stage consisted of the review according to themes related to the object of study, such as urban environmental impacts and the study of Brazilian metropolises, starting with legal documents that corroborated the process of creation and consolidation of the instruments. Then, the work consisted in the analysis of the instruments in two levels, the first referring to the isolated experience and the second, in a comparative way. The comparative and correlated analysis was based on some guiding variables: 1) Emergence Context; 2) Legal Basis; 3) Applicability (Scope, Prioritized Aspects and Score and Benefits). As part of the result, it was understood that the instruments have different objectives, mainly by QA aiming at reducing impacts within the municipality and floods, while QV proposes the maintenance of energy costs and impacts on the lot itself. In addition, the simplicity and versatility of QV in face of QA was noticed, however, not having the benefits in force, it does not become attractive. Finally, the differentiation in relation to the proposal of the instruments was understood, with the QA being mandatory for buildings with more than 500 m² and the QV also considered an optional seal.
Analisys of environmental qualification instruments applicable to build urban lots: the cases of Quota Ambiental, in the city of São Paulo (SP) and Qualiverde qualification, in the city of Rio de Janeiro (RJ)
Keywords: Crescimento urbano; Questões ambientais; Uso e ocupação do solo; Quota Ambiental; Qualiverde; Urban growth; Environmental issues; Land use and occupation; Qualiverde qualification; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL